Syntheses and Chiroptical Properties of Optically Active V‐Shaped Molecules Based on Planar Chiral [2.2]Paracyclophane. Issue 45 (3rd December 2021) - Miki, Nanami; Maeda, Hazuki; Inoue, Ryo; Morisaki, Yasuhiro
Abstract: Two optically active molecules were prepared using enantiopure planar chiral [2.2]paracyclophane as chiral building blocks, in which π‐electron systems were stacked at 120° to form a V‐shaped structure. The optical and chiroptical properties of the synthesized molecules were investigated experimentally and theoretically. The chiroptical properties depended strongly on the orientation of the stacked π‐electron systems; in other words, these properties could be regulated by changing the orientation of the stacked π‐electron systems. Abstract : Two kinds of optically active V‐shaped molecules were synthesized using enantiopure pseudo‐ meta ‐linked [2.2]paracyclophane building blocks. Two molecules emitted circularly polarized luminescence depending on the orientation of the stacked π‐electron systems.